PELAYANAN BIMBINGAN KONSELING DALAM MENGATASI KESULITAN BELAJAR SISWA - Aripin Aripin; Muslim Aswari; Andi Amza (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
The purpose of this study was to find out and analyze the learning difficulties experienced by students in the learning process at MTs Negeri 1 Palembang, in this study using a type of qualitative research by analyzing the management functions of counseling guidance services that had been applied at MTs Negeri 1 Palembang. The results of this study indicate that the form of learning difficulties experienced by students at MTs Negeri 1 Palembang. Learning difficulties in the form of learning disorder have never happened in the 2018-2019 school year. Factors that Become the Cause of Students Learning Difficulties at MTs Negeri 1 Palembang.Case of learning disorder. Evaluation is carried out through collaboration with the student's homeroom teacher, by means of intense communication related to the development of children who have learning difficulties.